The Influence of Student Development Understanding on Mathematics Education Students’ Readiness to Manage Diverse Classrooms - Saraswati Haylian Chiani; Wiwin Putriawati; Rahmawati (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study aims to analyze the influence of students’ understanding of child development theories on their readiness to manage diverse classrooms. The research was conducted on 28 mathematics education students who had completed the child development course at STKIP Paracendekia NW Sumbawa. A Likert-scale questionnaire was used as the instrument in a quantitative descriptive study. Following validity and reliability testing, all items on the instrument were deemed reliable (Cronbach's Alpha > 0.6) and valid (r > 0.301). With average scores ranging from 3.2 to 4.0, descriptive analysis revealed that the students' comprehension of child development and their preparedness to oversee diverse classrooms were both at good levels. The highest score appeared on items related to the importance of developmental understanding for creating inclusive learning environments, while the lowest was on the ability to adapt teaching methods. Classroom management readiness and knowledge of child development were shown to be strongly and significantly correlated by Pearson correlation analysis (r = 0.83, p < 0.001). Additionally, a basic linear regression study revealed that almost 70% of the variance in classroom management readiness could be explained by knowledge of child development (R2 = 0.70). The regression equation found was Y = 0.84X + 0.56. These results validate that one of the most important indicators of future teachers' preparedness is their understanding of cognitive, social, and emotional development. In order to improve pedagogical competence and responsiveness in managing various learners, the study emphasizes the significance of incorporating developmental psychology into teacher education courses.